The Mechanism of Caseinolytic Protease (ClpP) Inhibition1. Issue 10 (30th January 2013) - Gersch, Malte; Gut, Felix; Korotkov, Vadim S.; Lehmann, Johannes; Böttcher, Thomas; Rusch, Marion; Hedberg, Christian; Waldmann, Herbert; Klebe, Gerhard; Sieber, Stephan A.
<x xml:space="preserve">Abstract</x> Catch me if you can: The ClpP protease mediates protein homeostasis and can be efficiently inhibited by β‐lactones. A combination of molecular docking, mutagenesis, activity‐based protein profiling, and kinetics studies now reveals the mechanism of ClpP inhibition. A hydrophobic pocket next to the active site allows binding of long aliphatic and aromatic residues. The preferred stereoisomer binds into the oxyanion hole.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>